2018 International Consensus Statement on Golf and Health to guide action by people, policymakers and the golf industry. Issue 22 (23rd September 2018) - Murray, Andrew D; Archibald, Daryll; Murray, Iain Robert; Hawkes, Roger A; Foster, Charlie; Barker, Kevin; Kelly, Paul; Grant, Liz; Mutrie, Nanette
Abstract : Scientific and public interest relating to golf and health has increased recently. Players, potential players, the golf industry and facilities, and decision makers will benefit from a better understanding of how to realise potential health benefits and minimise health issues related to golf. We outline an International Consensus on Golf and Health. A systematic literature review informed the development of a survey. Utilising modified Delphi methods, an expert panel of 25 persons including public health and golf industry leaders, took part in serial surveys providing feedback on suggested items, and proposing new items. Predefined criteria for agreement determined whether each item was included within each survey round and in the final consensus. The working group identiﬁed 79 scientifically supportable statement items from literature review and discussions. Twenty-five experts (100%) completed all three rounds of surveys, rating each item, and suggesting modifications and/or new items for inclusion in subsequent surveys. After three rounds, 83 items achieved consensus with each with >75% agreement and <10% disagreement. These items are included in the final International Consensus on Golf and Health. The final consensus presented here can inform scientific knowledge, and action plans for (1) golfers and potential golfers, (2) golf facilities and the golf industry, and (3) policy and decision makers external to golf. These outputs, if widely adopted, will contribute to an improved understanding of golf and health, and aid these groups in making evidence-informed decisions to improve health and well-being.